JEJAK HISTORIS NILAI-NILAI MULTIKULTURALISME DI KAMPUNG BUGIS BULELENG BALI DAN POTENSINYA SEBAGAI SUMBER BELAJAR SEJARAH DI SMA - Simatupang, Gavin Ar Rasyid; Arta, Ketut Sedana; Pardi, I Wayan (Widya Winayata : Jurnal Pendidikan Sejarah, 2024)
This research aims to explores the historical traces of various multicultural values in Kampung Bugis Subdistrict, Buleleng, Bali, and its potential as a learning sources in High School (SMA). The research methodology used in this study is an approach of qualitative descriptive method, which includes: (1) heuristics, search of historical sources, (2) criticism, means of acquiring credible sources,(3) interpretation, interpreting on existing historical sources, and (4) historiography, the writing of history. The multicultural dynamic of Kampung Bugis have been long influenced by Bugis people migration and trades between 1600s and 1800s, as well as the arrival of other ethnic groups such as the Chinese, Malays, Arabs, and Javanese. Multicultural values are widely practiced and spread across the communal life of Kampung Bugis community, encompassing through three values: tolerance, equality, and inclusion. These aspects of multiculturalism in Kampung Bugis Subdistrict could be use as a source of learning and education for High School (SMA): acceptance and respect for diversity, equality, inclusion, and tolerance, and intercultural development.